Academic supervision in integrated Islamic elementary schools during the COVID-19 Pandemic - Victorynie, Irnie; Othman, Azam; Sheikh Ahmad, Ismail; Hussien, Suhailah (Indonesian Journal of Islamic Education Studies (IJIES), 2022)
The COVID-19 pandemic has significantly impacted the education sector, including the execution of academic supervision in schools. This study investigates the academic supervision in two integrated Islamic elementary schools in Bekasi, Indonesia, during the COVID-19 pandemic. The research method employed a qualitative research design as a case study. The methodological triangulation included interviews, academic supervision observations, and document analysis used to collect data. A total of two informants were the principals from integrated Islamic elementary schools, which were purposefully chosen based on their academic supervision expertise. The data from the interviews were transcribed. Then, the data was examined using the Atlas.ti software program based on theme analysis. Following that, we carried out coding procedures and interpretation. The findings revealed that academic supervision was still carried out before the pandemic, albeit with certain limitations. Principals begin by arranging academic supervision plans and organizing a team of school supervisors. Moreover, this study highlighted a new model of applying academic supervision procedures at schools amid the pandemic.